Design and application of a connecting structure suitable for syringe and gastric tube nozzle (一种适用于注射器和胃管接管的连接结构的设计及应用) - YANG Feili (杨非利); LIU Jiao (刘娇); YU Ranran (于冉冉); MENG Xuanxuan (孟璇璇) (Journal of International Translational Medicine Limited, 2024)
Nasal feeding is one of the main ways of enteral nutrition, and it is an important way of providing liquid diet or elementary diet and preventing secondary injury caused by long-term intestinal exclusion. The nursing care of patients with clinical nasal feeding nutrition usually leads to the fact that nutrients cannot be effectively injected into patients aseptically. This study introduces the design and application of a connecting structure between syringe and gastric tube, which can not only ensure the sterile injection of nutrients, but also achieve the purpose of saving the use cost to a certain extent. (鼻饲营养是临床常见的营养支持方法之一, 能够为患者提供营养丰富的流质饮食或要素饮食, 保证患者摄入足够的蛋白质和热量, 还可避免肠道长期旷置造成的继发伤害。本研究介绍一款注射器和胃管接管连接结构的设计和使用方法, 其结构新颖, 呈分体式, 方便组合使用, 可再循环, 不仅提升了可操作空间, 且在一定程度上降低了使用成本。)